Whitehead's organic philosophy of science - Plamondon, Ann L. (State University of New York Press, 1979)
This work assumes that Leclerc has correctly interpreted the relationship of the earlier philosophy of science to the later philosophy of organism and that the "considerable change in Whitehead's theories about the problems of science" has yet to be elucidated. It is the purpose of the present work to set out passages from Whitehead's philosophy of organism in order to elaborate the philosophy of nature embodied in the metaphysics and to draw the implications of the metaphysics for present discussions in the philosophy of science.